Systemic Corticosteroid Therapy for Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis in Vietnam: Clinical Evaluation and Analysis of Serum Cytokines - Tran, Thi Huyen; Lan, Pham Thi; Khang, Tran Hau; Luong, Vu Huy (Open Access Macedonian Journal of Medical Sciences, 2022)
Abstract BACKGROUND: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis are severe cutaneous adverse drug reactions. There are some immunological and genetic factors which are believed to be involved in the pathogenesis of SJS/TEN. The treatment of SJS/TEN is still controversial in which several studies showed variable results. AIMS: To evaluate clinically the efficacy of systemic corticosteroid and to analyze some related cytokines in the treatment of SJS/TEN. METHODS: This open, pilot and uncontrolled study was conducted at National Hospital of Dermatology and Venereology, in Hanoi, Vietnam, from October 2017 to September 2019. Methylprednisolone was indicated from the first day of hospitalization with the dose of 0.5-2.5 mg/kg/day (calculated according to prednisolone dose) once daily. It was continued until the patients got re-epithelialization. The efficacy of methylprednisolone was evaluated by observing clinically and analyzing related cytokines before and after the treatment. RESULTS: The mean time of re-epithelialization was 15.9 days, of hospitalization was 15.9 days (range 5-30 days). There was no in-hospital mortality in this study. The most common complication was transient glycaemia (40.6%), there was no patient with sepsis. At the day of hospitalization, serum concentrations of TNF-α, IFN-γ, IL-2, IL-5, IL-13 and IL-10 were significantly higher than those at the day of re-epithelialization (p<0.05). Serum levels of IL-4, did not have significant differences between two time points (p>0.05). CONCLUSION: The systemic corticosteroid is a good choice in the treatment of SJS/TEN. It can reduce serum levels of some cytokines that help SJS/TEN patients with avoiding mortality.